Validity and Reliability Determination of the Persian Version of Prosthesis Evaluation in Individuals with Lower Limb Amputations Questionnaire - M. Adel Gomnam; M. Kamali; H. Mobaraki; H. Saeedi (Afarand Scholarly Publishing Institute, 2016)
Aims: Post-amputation rehabilitation can improve the quality of life. Prosthesis evaluation questionnaire (PEQ) has been designed to evaluate the prosthetic functioning and major aspects of the quality of life in persons with lower-limb amputations. The aim of this study was to translate the questionnaire into Persian and evaluate validity and reliability of the translation. Instrument & Methods: The study was done qualitatively and quantitatively. Firstly, prosthesis evaluation questionnaire was translated into Persian and localized. To evaluate formal validity, the questionnaire was completed by 17 lower-limb amputees referred to Kowsar orthotics and prosthesis center. Its content validity was evaluated by 15 prosthesis experts. Using test-retest method, the questionnaire was completed by 70 amputees referred to the center in 2015. The amputees were selected by simple non-probability method. The questionnaire was completed by 22 of the amputees after 2 weeks, again. Data was analyzed using Cronbach's alpha, relative repetition coefficient, and impact score. Findings: The impact score of all the items of the questionnaire was more than 1.5 and favorable. Excluding formal scale and relative repetition coefficient, Cronbach's alpha was more than the favorable level (0.7) in other scales. Conclusion: Validity and reliability of the Persian version of prosthesis evaluation questionnaire are favorable; and the version can be used to assess prosthesis and major aspects of the quality of life in the Iranian amputees.